2006
DOI: 10.3748/wjg.v12.i38.6216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of rapid urease test: Pronto Dry to detectH pyloriin patients with dyspepsia in several cities in Indonesia

Abstract: Pronto Dry seems promising as a diagnostic tool to detect H pylori more rapidly and accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…However, a previous report found that the prevalence of H. pylori infection in Indonesia was quite low (10·2%) even when patients taking proton pump inhibitors were excluded from the study population [22]. First, we could not obtain information about medications used by the study participants.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, a previous report found that the prevalence of H. pylori infection in Indonesia was quite low (10·2%) even when patients taking proton pump inhibitors were excluded from the study population [22]. First, we could not obtain information about medications used by the study participants.…”
Section: Discussionmentioning
confidence: 96%
“…However, the reported prevalence ranged from 0% to 68% [4,5]. Six studies included patients with dyspepsia [5,[20][21][22][23][24], whereas three other studies included study participants from the general population [4,19,25]. Six studies included patients with dyspepsia [5,[20][21][22][23][24], whereas three other studies included study participants from the general population [4,19,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that we have included patients who had been administered antibiotics, histamine-2 receptor antagonists (H2-blockers), or proton pump inhibitors, which can influence H. pylori infection prevalence. However, a previous report found the prevalence of H. pylori infection in Indonesia to be quite low (10.2%) even after patients taking proton pump inhibitors were excluded from the study population [ 10 ].…”
Section: Discussionmentioning
confidence: 99%